The LcKNAT1-LcEIL2/3 Regulatory Module Is Involved in Fruitlet Abscission in Litchi - Ma, Xingshuai; Ying, Peiyuan; He, Zidi; Wu, Hong; Li, Jianguo; Zhao, Minglei (Frontiers in Plant Science, 2022)
Large and premature organ abscission may limit the industrial development of fruit crops by causing serious economic losses. It is well accepted that ethylene (ET) is a strong inducer of organ abscission in plants. However, the mechanisms underlying the control of organ abscission by ethylene are largely unknown. We previously revealed that LcKNAT1, a KNOTTED-LIKE FROM ARABIDOPSIS THALIANA1 (KNAT1)-like protein, acted as a negative regulator in control of fruitlet abscission through suppressing the expression of ethylene biosynthetic genes in litchi. Here, we further reported that LcKNAT1 could also directly repress the transcription of LcEIL2 and LcEIL3, two ETHYLENE INSENSITIVE 3-like (EIL) homologs in litchi, which functioned as positive regulators in ET-activated fruitlet abscission via directly promoting the expression of genes responsible for ethylene biosynthesis and cell wall degradation. The expression level of LcKNAT1 was down-regulated, while LcEIL2/3 was up-regulated at abscission zone (AZ) accompanying the fruitlets abscission in litchi. Results of electrophoretic mobility shift assays and transient expression showed that LcKNAT1 could directly bind to the promoters of LcEIL2 and LcEIL3 and repress their expression. Furthermore, genetic cross demonstrated that the GUS expression driven by the promoters of LcEIL2 or LcEIL3 at the floral AZ was obviously suppressed by LcKNAT1 under stable transformation in Arabidopsis. Taken together, our findings suggest that the LcKNAT1-LcEIL2/3 regulatory module is likely involved in the fruitlet abscission in litchi, and we propose that LcKNAT1 could suppress both ethylene biosynthesis and signaling to regulate litchi fruit abscission.